2019
DOI: 10.1186/s40066-019-0251-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds, health benefits and utilization of Rhododendron: a comprehensive review

Abstract: The Rhododendron distributed throughout the world is a small evergreen tree with deep red or pale pink flowers, belongs to the family Ericaceae and is known for its spectacular flowers. The species is widely distributed between the latitudes 80°N and 20°S with high socioeconomic reverence and has been designated as the national flower of Nepal and state flower of Himachal Pradesh (India). In addition to its immense horticultural importance, it is commonly used as an ornamental plant for gardens, plantations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Many Rhododendron plants provide health benefits due to their significant bioactivity and have the potential to be utilized in the medicinal and food industries ( Kumar et al, 2019 ). As a dominant evergreen shrub, Rhododendron przewalskii is widely distributed on the Qinghai-Tibet Plateau, and the flowers and leaves of R. przewalskii are used by local people as folk medicine to treat lung diseases in clinics ( Yang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many Rhododendron plants provide health benefits due to their significant bioactivity and have the potential to be utilized in the medicinal and food industries ( Kumar et al, 2019 ). As a dominant evergreen shrub, Rhododendron przewalskii is widely distributed on the Qinghai-Tibet Plateau, and the flowers and leaves of R. przewalskii are used by local people as folk medicine to treat lung diseases in clinics ( Yang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many countries around the world have great sources of medicinal plants that have been used for centuries as a medicine to get rid of various diseases [1] . Over the last two decades, an increasing number of biological studies have been conducted related with the natural secondary metabolites found in herbs due to their supporting properties of modern medicine for the treatment of various diseases such as diabetes, hypertension, cardiovascular, neurodegenerative diseases, and even cancer [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Rhododendron is classified as the earliest of the flowering plants. It has been in existence for 800 million years ago (Vikas Kumar, 2019) .The first rhododendron was observed in the temperate zone of northern hemisphere and the fossil of oldest rhododendron was found in the southern China, in a place where three Chinese province of Yunnan, Sichuan and Tibet meet (Wang et al, 2014) the area is situated around 1000 kilometers of Nepal). The first rhododendron was brought into Britain in 1656 from the European Alps, where the plant was classified and named as Rhododendron hirsutum.…”
Section: Introductionmentioning
confidence: 99%